Chaihu and Longgu Muli Decoction demonstrate neuroprotective effects in the rat model of Parkinson's disease with depression by regulating the AMPK/mTOR signaling pathway - Wei Liu; Junling Cao; Jingfeng Ouyang; Mengxia Yin; Tuotuo Cui; Xin Liu; Yujuan Li; Ying Huang; Zhiwei Jing (Elsevier, 2023)
Background: Chaihu and Longgu Muli decoction (CLMD) has been used as a classical prescription of traditional Chinese medicine (TCM) prescription to treat Parkinson's disease with depression (PDD). Nevertheless, the potential mechanisms underlying their neuroprotective effects are not well-understood. Purpose: To evaluate the neuroprotective effects and possible involvement of a molecular signaling pathway of CLMD in a PDD rat model. Methods: Adult male SD rats were randomly divided into six groups: control, model, positive (madopar 0.032 g kg−1 day−1), low dosage (L, 5 g kg−1 day−1), medium dosage (M, 10 g kg−1 day−1) and high dosage (H, 20 g kg−1 day−1) of CLMD. The neuroprotective effects of CLMD were investigated using behavioral tests, immunohistochemistry, immunofluorescence, high-performance liquid chromatography (HPLC), and Nissl staining. Western blotting was used to further investigate the mechanism of action of CLMD. The protein expression of LC3, AMPK, p-AMPK, mTOR, and p-mTOR were examined. Results: CLMD exhibited a protective effect on dopaminergic neurons by increasing the expression of tyrosine hydroxylase, which was predicted to be decreased by rotenone. CLMD restored behavior impaired by rotenone and increased the degradation of α-Syn aggregation to reduce tyrosine hydroxylase loss. Additionally, it upregulated the expression of LC3, p-AMPK/AMPK, and downregulated the expression of p-mTOR/mTOR. Conclusion: : These findings provide evidence that CLMD restored behavior performance, protected dopaminergic neurons and activated autophagy by regulating the AMPK/mTOR signaling pathway in rat model of PDD. CLMD restored behavior and protected dopaminergic neurons by regulating the AMPK/mTOR signaling pathway to induce autophagy and inhibit apoptotic activity.